Živnostenský zákon : komentář - Solomonová, Kristýna, 1982-; Balada, Lukáš, 1985-; Kunštátová, Tatiana, 1953-; Dickelt, František, 1978- (C.H. Beck, 2023)
Komentované znění zákona o živnostenském podnikání.
Keywords: živnostenské podnikání -- Česko; business enterprises -- Czechia; zákony; komentáře; laws; commentaries